Comparative Study between Scales: Subjective Elbow Value and Patient-rated Tennis Elbow Evaluation Applied to Patients Affected by Lateral Epicondylitis - Roberto Yukio Ikemoto; Luiz Henrique Oliveira Almeida; Giovanna Galvão Braga Motta; Alexandre Se Moo Kim; Carlos Vitor Nunes Lial; Johny James Claros (Revista Brasileira de Ortopedia)
Abstract Objective To verify if the subjective elbow value (SEV) scale presents similar results to those of the Patient-rated Tennis Elbow Evaluation (PRTEE) scale in the evaluation of patients with lateral elbow epicondylitis (LEE). Methods Thirty-seven patients were diagnosed with LEE in the outpatient service of our hospital through clinical history, physical examination, X-ray, and ultrasonography. The SEV and PRTEE scales were used and their results were compared using a significance level ≥ 5% (p ≥0.05). Results A statistically significant relationship was found between the values of SEV and PRTEE in the group of patients studied (p= 0.017). Conclusion Subjective elbow value presented similar results to PRTEE in the evaluation of patients with diagnosis of LEE.